2015
DOI: 10.1146/annurev-immunol-032414-112248
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Necrosis in the Cross Talk of Cell Death and Inflammation

Abstract: Cell proliferation and cell death are integral elements in maintaining homeostatic balance in metazoans. Disease pathologies ensue when these processes are disturbed. A plethora of evidence indicates that malfunction of cell death can lead to inflammation, autoimmunity or immuno-deficiency. Programmed necrosis or necroptosis is a form of non-apoptotic cell death driven by the receptor interacting protein kinase 3 (RIPK3) and its substrate mixed lineage kinase domain-like (MLKL). RIPK3 partners with its upstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
288
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 308 publications
(296 citation statements)
references
References 191 publications
(225 reference statements)
4
288
1
3
Order By: Relevance
“…As a consequence, rupture of plasma membranes was evident from our studies, which ultimately results into significant losses of intracellular contents [67][68][69]. Moreover, similar experimentation in a rodent model system showed very similar characteristics in arterial and cardiac muscles, under high power TEM.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…As a consequence, rupture of plasma membranes was evident from our studies, which ultimately results into significant losses of intracellular contents [67][68][69]. Moreover, similar experimentation in a rodent model system showed very similar characteristics in arterial and cardiac muscles, under high power TEM.…”
supporting
confidence: 61%
“…Employing transmission electron microscopy (TEM), in our Mg-deficient rabbit experimentation suggested to us that, both the vascular smooth muscle cells and macrophages of the lipid-laden arterial vessels exhibited necrosis and apoptosis [16,65,66, unpublished findings of Stempak, BT Altura, M Brust and BM Altura]. Further, investigation using TEM on cardiac and arterial muscle cells of Mg-deficient rats also showed clear signs of necrosis as well as apoptosis [66][67][68][69][70][71][72][73][74][75][76][77][78]; N Shah, BT Altura and BM Altura, unpublished findings]. Experimentation with high-power TEM revealed that, these Mg-deficient muscle cells exhibited what is now termed "necroptosis".…”
mentioning
confidence: 91%
“…Necroptosis is a programmed form of necrosis, characterized by the rounding of the cell, gaining in cell volume, rupture of plasma membrane and release of intracellular contents [1,2]. Distinct from apoptosis, which is executed by proteases of the caspase family, necroptosis is thought to be a form of protease-independent cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Caspase-dependent apoptosis is a key cell death module with important functions in development and certain disease pathologies. In addition to apoptosis, recent evidence shows that a form of regulated necrosis, termed necroptosis, is significantly associated with a number of common clinical diseases such as viral infection, ischemia-reperfusion injury, myocardial infarction, atherosclerosis, and inflammatory bowel diseases (1,2). Necroptosis is driven by the cytosolic serine/threonine kinase receptor-interacting protein kinase 3 (RIPK3) 2 (3).…”
mentioning
confidence: 99%
“…Necroptosis is driven by the cytosolic serine/threonine kinase receptor-interacting protein kinase 3 (RIPK3) 2 (3). A wide variety of stimuli including tumor necrosis factor (TNF) superfamily death ligands have been reported to induce necroptosis (1). Ligation of TNF to TNF receptor (TNFR) 1 causes formation of receptor-associated complex I, which comprises of TNFR1-associated via death domain (TRADD), TNFR-associated factor 2 (TRAF2), cellular inhibitor of apoptosis 1 (cIAP1), cIAP2, linear ubiquitin chain assembly complex (LUBAC), and RIPK1.…”
mentioning
confidence: 99%